2008
DOI: 10.1016/j.jat.2008.04.011
|View full text |Cite
|
Sign up to set email alerts
|

A de Montessus type convergence study of a least-squares vector-valued rational interpolation procedure

Abstract: In a recent paper of the author [A. Sidi, A new approach to vector-valued rational interpolation, J. Approx. Theory 130 (2004) 177-187], three new interpolation procedures for vector-valued functions F(z), where F : C → C N , were proposed, and some of their algebraic properties were studied. One of these procedures, denoted IMPE, was defined via the solution of a linear least-squares problem. In the present work, we concentrate on IMPE, and study its convergence properties when it is applied to meromorphic fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…, p. However, the quality of R p,k (z) as an approximation to F (z) in the z-plane depends heavily on how the c j are chosen. Thus, the methods IMPE, IMMPE, and ITEA choose the c j in special ways; as we have shown in [6], [7], and [8], the methods IMPE and IMMPE do provide very good approximations for meromorphic functions F (z). Here we prove that ITEA does too.…”
Section: Review Of the Algebraic Properties Of Iteamentioning
confidence: 82%
See 1 more Smart Citation
“…, p. However, the quality of R p,k (z) as an approximation to F (z) in the z-plane depends heavily on how the c j are chosen. Thus, the methods IMPE, IMMPE, and ITEA choose the c j in special ways; as we have shown in [6], [7], and [8], the methods IMPE and IMMPE do provide very good approximations for meromorphic functions F (z). Here we prove that ITEA does too.…”
Section: Review Of the Algebraic Properties Of Iteamentioning
confidence: 82%
“…Some of the algebraic properties of these methods were already presented in [4] while others were explored in [5], where it was also shown that the methods are symmetric functions of the points of interpolation and that they reproduce vectorvalued rational functions exactly. In [6], [7], and [8], de Montessus and König type convergence theories for IMMPE and IMPE, as these methods are applied to vectorvalued meromorphic functions with simple poles, were presented. In this work, we treat the convergence properties of ITEA, as it is being applied to the same class of functions, and we prove de Montessus and König type theorems analogous to those for IMPE and IMMPE.…”
Section: Introductionmentioning
confidence: 99%
“…Using the Vieta formulas connecting the coefficients of a polynomial and its zeros it follows that there exists C 1 ≥ 1 such that (10) sup 10) and (11) imply that…”
Section: Letmentioning
confidence: 99%
“…In this second direction a significant contribution is due to Graves-Morris/Saff in [8] where they prove an analogue of the Montessus de Ballore theorem which plays a central role in the classical theory of Padé approximation. See also [9]- [10] for different approaches to the same type of results as well as [11] and references therein for least-squares versions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we may have apriori knowledge of the location of some of the poles of f and we can use this information to fix some of the zeros of Q n,m at such points. Another possibility is to combine two (or more) approximation criteria to define the rational functions; for example, interpolation at a fixed number of points and the L 2 construction (or viceversa as in [8] and te references therein).…”
Section: Incomplete Fourier-padé Approximantsmentioning
confidence: 99%